Failure mode and effects analysis and fault tree analysis of surface image guided cranial radiosurgery. Issue 5 (20th April 2015) - Manger, Ryan P.; Paxton, Adam B.; Pawlicki, Todd; Kim, Gwe‐Ya
Abstract : Purpose: Surface image guided, Linac‐based radiosurgery (SIG‐RS) is a modern approach for delivering radiosurgery that utilizes optical stereoscopic imaging to monitor the surface of the patient during treatment in lieu of using a head frame for patient immobilization. Considering the novelty of the SIG‐RS approach and the severity of errors associated with delivery of large doses per fraction, a risk assessment should be conducted to identify potential hazards, determine their causes, and formulate mitigation strategies. The purpose of this work is to investigate SIG‐RS using the combined application of failure modes and effects analysis (FMEA) and fault tree analysis (FTA), report on the effort required to complete the analysis, and evaluate the use of FTA in conjunction with FMEA. Methods: A multidisciplinary team was assembled to conduct the FMEA on the SIG‐RS process. A process map detailing the steps of the SIG‐RS was created to guide the FMEA. Failure modes were determined for each step in the SIG‐RS process, and risk priority numbers (RPNs) were estimated for each failure mode to facilitate risk stratification. The failure modes were ranked by RPN, and FTA was used to determine the root factors contributing to the riskiest failure modes. Using the FTA, mitigation strategies were formulated to address the root factors and reduce the risk of the process. The RPNs were re‐estimated based on the mitigation strategies to determine the margin of risk reduction. Results: The FMEA and FTAs for the top two failure modes required an effort of 36 person‐hours (30 person‐hours for the FMEA and 6 person‐hours for two FTAs). The SIG‐RS process consisted of 13 major subprocesses and 91 steps, which amounted to 167 failure modes. Of the 91 steps, 16 were directly related to surface imaging. Twenty‐five failure modes resulted in a RPN of 100 or greater. Only one of these top 25 failure modes was specific to surface imaging. The riskiest surface imaging failure mode had an overall RPN‐rank of eighth. Mitigation strategies for the top failure mode decreased the RPN from 288 to 72. Conclusions: Based on the FMEA performed in this work, the use of surface imaging for monitoring intrafraction position in Linac‐based stereotactic radiosurgery (SRS) did not greatly increase the risk of the Linac‐based SRS process. In some cases, SIG helped to reduce the risk of Linac‐based RS. The FMEA was augmented by the use of FTA since it divided the failure modes into their fundamental components, which simplified the task of developing mitigation strategies.